Experience of a tertiary acute care hospital in Southeast Asia in initiating patient engagement with the aid of digital solutions - Fan, Peijin Esther Monica; Lim, Shu Hui; Sim, Guan Hua Jonathan; Poticar, Mary Jane Seville; Kam, Wee Fang; Leong, Yee Fenn Rena; Choy, Xin Yi Selene; Ong, Lay Teng; Wang, Xia; Lau, Soy Soy; Ng, Gaik Nai; Ayre, Tracy Carol; et al. (Frontiers in Health Services, 2024)
IntroductionWith the goal of patient engagement, an initiative was formulated to equip each patient in the general wards with a tablet whereby they can access their health information and patient education materials and communicate with their healthcare team. This paper presented the methodology of the implementation efforts as well as an evaluation of the preliminary outcomes.MethodsThe process of hospital-wide implementation was shared using the implementation research logic model. The bedside tablets were rolled out hospital-wide in a step-wedge manner over 12 months. Barriers and facilitators to this implementation were discussed together with strategies to optimize the situation. Preliminary outcomes of the implementation were evaluated using the RE-AIM framework.ResultsThe initial adoption rate for the bedside tablet was low. Additional strategies, such as survey audits and provision of feedback, development of education materials for patients, facilitation, and purposefully re-examining the implementation strategies, were used to improve adoption. The trend of adoption increased over the course of 2 years from the start of implementation.DiscussionThe initial lower adoption rates may reflect Singapore's paternalistic healthcare culture. While this implementation was driven by the need to move away from paternalism and toward patient engagement, more time is required for significant cultural change.